Treatment of lower urinary tract dysfunction in patients with multiple sclerosis. Committee of the European Study Group of SUDIMS (Sexual and Urological Disorders in Multiple Sclerosis) - Fowler, C J (1992)
Bladder symptoms in patients with multiple sclerosis (MS) are common and usually arise as a result of spinal lesions which interrupt the neural pathways connecting the pontine micturition centre to the sacral spinal cord. Thus these symptoms are particularly likely to occur in those with lower limb neurological deficits. Fortunately bladder dysfunction in MS is rarely associated with serious upper tract disease so that the problem is usually one of symptomatic management. Lower urinary tract symptoms may be both "irritative" or "obstructive" in nature and can be explained in terms of underlying detrusor hyperreflexia and incomplete bladder emptying. Treatment is aimed at minimising both these effects. Oral anticholinergic medication can be effective in reducing detrusor hyperreflexia and intermittent catheterisation is used to reduce abnormally high post micturition residual volumes. With this simple treatment, often used in combination, many less severely affected patients with MS can gain considerable improvement in controlling urinary continence.